DEVELOPMENT OF MINI / MICRO HYDRO POWER PLANT FOR RURAL ELECTRICITY IN INDONESIA - Hardjomuljadi, Sarwono; D. Siswoyo, Sriyono (Agency for the Assessment and Application of Technology)
Indonesia has a lot of water energy resources, some of it could be developed for rural mini / micro hydro power plant. The resources have been estimated to be able to provide electricity of 74,976 MW capacities with annual energy output equal to 401 billion kWh. However, it is only 5% that has been exploited for electricity, 62% in Java and 38% outside Java. This shows that the opportunity to develop electricity from water resources is widely opened especially outside Java. The increase price of fossil fuel has shown an important drive to explore the alternative energy. Development of rural electricity could be initiated by developing mini / micro hydro power plant (PLTMH) in rural area either by PLN or by Private Sector of Middle Small Industry (rural UKM) or by Rural Co-Operative. Schemes to push development of PLTMH have been introduced by the Government and in some areas have been working successfully. Some constraints have been identified and with right and good governance, it is believed that participation of rural society in development of PLTMH to support rural electricity will work successfully.